The first complete chloroplast genome sequence of Pteroceltis tatarinowii (Ulmaceae), an endangered tertiary relict tree endemic to China - Yunyan Zhang; Guozheng Wang; Jiehan Zhou; Xinpeng Zhou; Pengfu Li; Zhongsheng Wang (Mitochondrial DNA. Part B. Resources, 2019)
Pteroceltis tatarinowii is an endangered Tertiary relict tree endemic to China with high ecological and economic value. Meanwhile, P. tatarinowii is the sole representative of the genus Pteroceltis Maxim., thus it is of great importance to the phylogenetic studies of Ulmaceae. Here, we first conducted the paired-end shotgun sequencing of P. tatarinowii on the Illumina HiSeq platform. Based on the resulting sequence, the complete chloroplast (cp) genome of P. tatarinowii was 158,635 bp long and displayed a typical quadripartite structure consisting of a pair of inverted repeats (IRs) with a length of 26,020 bp, separating by two single-copy regions (LSC, 87,627 bp and SSC, 18,968 bp). Besides, it encoded 119 genes, including 80 protein-coding genes, 29 transfer RNAs, eight ribosomal RNAs, and two pseudogenes. Moreover, a maximum likelihood (ML) phylogenetic analysis based on the 14 cp genomes revealed that P. tatarinowii was closely related to the genus Cannabis and the Ulmaceae species did not form a monophyletic clade.